Making a scene - Wu, Constance, 1982- (Scribner, 2022)
"Through raw and relatable essays, Constance shares private memories of childhood, young love and heartbreak, sexual assault and harassment, and how she "made it" in Hollywood. Her stories offer a behind-the-scenes look at being Asian American in the entertainment industry and the continuing evolution of her identity and influence in the public eye"--